PENGARUH PEROKOK AKTIF DIATAS 5 TAHUN TERHADAP KADAR HEMOGLOBIN DI KECAMATAN PANYILEUKAN KOTA BANDUNG - Dwika Tifanni Arifin; M. Ali Yunasri (Sekolah Tinggi Pariwisata Mataram, 2021)
Indonesian people cigarette consumption is high enough, one out of three Indonesian people smoke. Smoking is the act of sucking smoke from burning tobacco. The prevalence of smoke in Indonesian has increased from year to year. The habit of smoking and inhaling cigarette smoke from burning cigarettes will have a negative impact on the health of many people, ranging from active smokers to passive smokers. One of them will have an impact on the effect of hemoglobin levels in the blood. The purpose of this study was to see the effect of active smokers over 5 years on hemoglobin levels. The type of research used is analytic observational research with a cross sectional approach. The sample in this study were male residents in the Panyileukan sub-district, Bandung City, which consisted of 30 respondents who were active smokers over 5 years which were taken by purposive sampling.The results showed that in 30 samples of active smokers, 21 samples (70%) had normal hemoglobin levels, 3 samples (20%) had low hemoglobin levels, and 6 samples (10%) had high (abnormal) hemoglobin levels.The conclusion of this study was that 30 blood samples of active smokers over 5 years had normal hemoglobin levels, although in some samples there were low and high hemoglobin levels.